Delivery Routes for COVID-19 Vaccines - Jang Hyun Park; Heung Kyu Lee (Vaccines, 2021)
The novel coronavirus, SARS-CoV-2, which causes COVID-19, has resulted in a pandemic with millions of deaths. To eradicate SARS-CoV-2 and prevent further infections, many vaccine candidates have been developed. These vaccines include not only traditional subunit vaccines and attenuated or inactivated viral vaccines but also nucleic acid and viral vector vaccines. In contrast to the diversity in the platform technology, the delivery of vaccines is limited to intramuscular vaccination. Although intramuscular vaccination is safe and effective, mucosal vaccination could improve the local immune responses that block the spread of pathogens. However, a lack of understanding of mucosal immunity combined with the urgent need for a COVID-19 vaccine has resulted in only intramuscular vaccinations. In this review, we summarize the history of vaccines, current progress in COVID-19 vaccine technology, and the status of intranasal COVID-19 vaccines. Future research should determine the most effective route for vaccine delivery based on the platform and determine the mechanisms that underlie the efficacy of different delivery routes.